Relapse risk after autologous transplantation in patients with newly diagnosed myeloma is not related with infused tumor cell load and the outcome is not improved by CD34+ cell selection: long term follow-up of an EBMT phase III randomized study - Bourhis, Jean-Henri; Bouko, Yasmina; Koscielny, Serge; Bakkus, Marleen; Greinix, Hildegard; Derigs, Gunter; Salles, Gilles; Feremans, Walter; Apperley, Jane; Samson, Diana; Björkstrand, Bo; Niederwieser, Dietger; et al. (Haematologica, the hematology journal, 2007)
Background and Objectives This European Group for Blood and Marrow Transplantation (EBMT) multicentre randomized phase III study was designed to assess the safety and efficacy of CD34+ selection in newly diagnosed myeloma patients undergoing autologous transplantation.Design and Methods One hundred and eleven patients responsive to initial chemotherapy were randomized to receive CD34+ selected (arm A) or unselected PBPC (arm B) after conditioning with high-dose melphalan and TBI. ASO-PCR was used to assess purging efficacy and reinfused tumor load. Tumor load could be assessed in 59 patients.Results CD34+ selection gave a median tumor cell depletion of 2.2 logs (0.77-5.96). No tumor cells were detected in products infused in 17/26 (A) and 5/33 (B) patients. The five year overall survival (OS), event free survival (EFS) and relapse rate (RR) were 51%, 20% and 80% in arm A and 45%, 18% and 80% in arm B respectively with no significant difference between the two groups. Thirteen patients in arm A and 2 in arm B experienced episodes of serious early infection (p=0.02). There were 3 early transplant related deaths in A but none in B.Interpretation and Conclusions Despite significant tumor cell reduction, CD34+ selection does not reduce RR and increases the risk of severe post-transplant infections. There was also no difference in RR between patients in either arm who received grafts with detectable tumor cells and those receiving grafts with no detectable tumor cells, suggesting that reinfused tumor cells may not be the main cause of relapse after autologous transplant in myeloma.
Gesehen am 21.01.2022